G76 Identifying challenges with paediatric procedural sedation in the ed setting in ireland and the uk: a paediatric emergency research in the united kingdom and ireland (peruki) study. (27th April 2015) - McCoy, S; Lyttle, M; Hartshorn, S; Larkin, P; Brenner, M; O'Sullivan, R
Abstract : Aims: There is extensive literature on paediatric procedural sedation (PPS) and its clinical applications in Emergency Departments (EDs). While numerous guidance and policy documents exist from international bodies, there remains a lack of uniformity and consistency of PPS practices within EDs. PPS is now gaining traction in the UK and Ireland and this study aimed to describe existing PPS practices and identify any challenges to ED-based PPS. Methods: A qualitative approach was employed to capture data through a focus group interview. Nine specialists in Emergency Medicine (EM) participated, varying in years of experience, clinical settings (mixed adult and paediatric ED or paediatric only) and geographical location (UK and Ireland). The focus group, conducted at the College of Emergency Medicine annual meeting in London in 2013, was audio-recorded, transcribed verbatim and analysed using Attride-Stirling's framework for thematic network analysis. Ethical approval was not required for this study. Results: The global theme 'The Future of Paediatric Procedural Sedation (PPS) in Emergency Medicine – A UK and Ireland perspective' emerged from the following three organising themes: 1) training and education of ED staff; 2) current realities of PPS in EDs and 3) procedural sedation and the wider hospital community. The main findings were: there is significant variability in ED sedation practice throughout the UK and Ireland; lack of formal training in PPS at a trainee level is a barrier to its implementation as a standard treatment; there is a lack of recognition of PPS at a college/training level as a specialised emergency medicine skill. Conclusion: Emergency Medicine must take ownership of PPS as a core competency. This can be acheived by embedding procedural sedation training into general and paediatric EM training. Coupled with EM-led research and audit of sedation practice.